Three new Procamallanus (Spirocamallanus) species from freshwater fishes in Mexico - Moravec, F; Salgado-Maldonado, G; Caspeta-Mandujano, J (The Journal of parasitology, 2000)
The following 3 new species of Procamallanus (Spirocamallanus) are described from the intestines of freshwater fishes in Mexico, all belonging to the morphological group characterized by the presence of wide caudal alae, 3 pairs of subventral preanal papillae, and unequal spicules in the male: Procamallanus (Spirocamallanus) jaliscensis n. sp. (type host: Agonostomus monticola) and Procamallanus (Spirocamallanus) gobiomori n. sp. (hosts: Gobiomorus maculatus [type host], Gobiomorus polylepis and Eleotris picta) from 2 rivers in Jalisco State, western Mexico, and Procamallanus (Spirocamallanus) mexicanus n. sp. (type host: Cichlasoma geddesi) from Xalapa District, Veracruz State (Gulf of Mexico region), southeastern Mexico. Procamallanus jaliscensis is characterized by the length of the spicules (606-900 microm and 282-354 microm), number (15-16) of spiral ridges in the buccal capsule, and the digit-like protrusion with 1 terminal cuticular spike on the female tail; P. mexicanus by the length of the spicules (456-480 microm and 231-233 microm), number (10-12) of spiral ridges in the capsule, and the shape of the female tail (conical with a suddenly narrowed distal part, without any terminal spikes); and P. gobiomori by the length of spicules (318-348 microm and 156-192 microm), number (8-10) of spiral ridges and by the digit-like protrusion with 2 terminal cuticular spikes on the female tail.
Keywords: nemoci ryb; Fish Diseases; Female; Nematoda; Intestinal Diseases, Parasitic; zvířata; Mexico; nematodózy; sladká voda; hlístice; Mexiko; ženské pohlaví; Male; Fresh Water; Animals; Nematode Infections; mužské pohlaví; Perciformes; parazitární nemoci střev